The Concept of Innovation Classes Through The Parent Partnership Model at School - Fauziah, Pujiyanti; Kusumawardani, Erma (Universitas Negeri Semarang, 2019)
This Study describes the concept of parent class innovation through peer parent mentor in high school. This research was conducted by a qualitative approach. A preliminary study was conducted in four high school and vocational schools in Yogyakarta. The focus of this research was on parent class activities that became one of the forms of a partnership model with a parent in school. Researcher as an instrument in this study by used guidelines interview, observation, and study documentation to collect data and information. The interactive analysis was chosen by the researcher as a technique in data analysis obtained. The result of this research was the concept of implementation of parent class in high school. Then the researcher makes a concept of peer parent mentor used a theory about mentoring. So, the concept peer parent mentor can use to optimize the implementation of the parent class. The implementation of these methods starts from the planning stage until evaluation.